Air-assistance and low volume application to control of asian rust on soybean crop - De Souza Christovam, Rafael [UNESP]; Raetano, Carlos [UNESP]; Prado, Evandro [UNESP]; Dal Pogetto, Mário [UNESP]; Júnior, Hélio [UNESP]; Gimenes, Marcelo [UNESP]; Serra, Marina [UNESP] (Polish Academy of Sciences Chancellery, 2010)
Currently, one of factors that cause the production cost increase of soybean crop is the pesticide application. The most important disease in soybean crop is Asian rust, caused by Phakopsora pachyrhizi Sydon & P. Sydon fungus, which can cause significant loss of the production. Therefore, this work aimed at evaluation of different spraying techniques on the spray deposits and some parameters of soybean crop: grain size, weight of 1 000 seeds and the crop productivity. Two experiments were carried out in the experimental area of FCA/UNESP (Faculdade de Ciencias Agronomicas/Universidade Estadual Paulista Julio de Mesquita Filho) - Botucatu, S P, Brazil, in soybean crop, Conquista variety, in the 2007/2008 season. In the first experiment, three air levels (0, 9 and 29 km/h of the air speed generated by fan) with flat fan nozzle XR 8002 with a spray volume of 130 l/ha were compared with a rotating nozzle - using low volume oily - LVO at 40 l/ha of spray volume. The second experiment was carried out under the same conditions as the previous experiment, including a control treatment (untreated plants). The disease severity was evaluated using a diagrammatic scale with a visual evaluation of the disease on 15 leaves of each plot. The grades varied between 0.6 and 78.5% of the disease severity. The use of air assistance when compared with the rotating system nozzle did not show significant differences for spray deposits on adaxial and abaxial surface of the leaves in bottom part of the plant. The air assistance with maximum air speed (29 km/h) increased the productivity with respect of the other treatments.
Keywords: low volume oily; pest control; productivity; spray technology; Fungi; Glycine max; Phakopsora pachyrhizi